Postoperative corneal asphericity in low, moderate, and high myopic eyes after transepithelial PRK using a new pulse allocation - Lin, David T. C.; Holland, Simon P.; Verma, Shwetabh; Hogden, John; Arba Mosquera, Samuel (Journal of refractive surgery, 2017)
Journal of Refractive Surgery | PURPOSE:To evaluate the postoperative asphericity in low, moderate, and high myopic eyes after combined transepithelial photorefractive keratectomy and SmartSurfACE treatment (SCHWIND eye-tech-solutions GmbH, Kleinostheim, Germany).METHODS:In this retrospective case series, the outcomes of myopic SmartSurfACE were evaluated at 3 months postoperatively in 106 eyes and divided into low (less than